MULHERES NAS CIÊNCIAS: UMA QUESTÃO DE GÊNERO? - Santos, Cristina Silva dos; Radl-Philpp, Rita Maria; Vieira, Zoraide Santos (Revista de Estudos em Educação e Diversidade - REED, 2022)
We propose, through this article, to analyze the insertion of women in the teaching process, as well as to reflect on the dynamization and popularization of public policies of higher education directed to the Exact Sciences. We opted for a qualitative approach, based on the bibliographic research and main interlocutors Simone de Beauvoir (1980), Radl-Philpp (2008; 2010; 2013) and Louro (2007; 2001), in addition to resorting to the CNPq (National Council of Scientific and Technological Development) among other technological resources to identify the participation of men and women in programs to offer resources for research fellows in the areas of Exact Sciences. We realize that only by encouraging studies in the exact sciences area will we be able to overcome the existing segregation process between men and women. The biological and social constructs traced by society show a process of exclusion experienced by women. Policies and programs established by the government and by teaching and research institutions can significantly contribute to reducing women’s social exclusion